El órgano de la Basílica de Chiquinquirá: 125 años. Pesquisas que reconstruyen su historia (2020)
This article contributes to reconstructing the history of one of the largest pipe organs brought to the country in the xix century: the organ of the Basilica of Our Lady of the Rosary of Chiquinquirá. Based on bibliographic, newspaper, documentary, and testimonial sources, it presents data about the Amezua house, as well as information about the role played by people such as the presbyter Lorenzo de Elcoro and don Juan Suárez Elcoro. It is mainly based on research works on Spanish organ building at the time, as well as on serial publications from the end of the xix century and texts on the history of the Virgin of Chiquinquirá and her Sanctuary. The article confirms the existence of four of these organs in Colombia. It also presents unpublished photographs, one of which could be the oldest visual record that exists of the organ in the Bogotá Cathedral (1891) and its first performer. Finally, it also alludes to the first chapel master of the Basilica of Chiquinquirá and to some musicians who succeeded him in this profession; at the same time, it emphasizes the importance of the first musical compositions written in honor of the Virgin of the Rosary of Chiquinquirá and encourages the retrieval of this historical musical archive.